2013
DOI: 10.3109/13697137.2013.864268
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine resistance in breast cancer

Abstract: Selective estrogen receptor modulators (SERMs) are synthetic molecules which bind to estrogen receptors (ER) and can modulate their transcriptional capabilities in different ways in diverse estrogen target tissues. Unfortunately, the use of resistant therapy is associated with acquired resistance. Several molecular mechanisms have been proposed to be responsible for endocrine resistance in breast cancer, including MIR-451, FGF and FGFR, ADAM12, fibronectin and other soluble stromal factors, PELP1-KDM1, HER2, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…COL4 was absent from the tumor stroma, with only perivascular COL4 observed (Figure 1E ). Accompanying these changes in ECM composition, heterogeneous breast cancer microenvironments are enriched with hormones (Garcia-Robles et al, 2013 ; Simões et al, 2015 ), growth factors (Mimeault et al, 2007 ; Ye et al, 2009 ; Zheng et al, 2014 ; Ho-Yen et al, 2015 ; Voudouri et al, 2015 ), cytokines (Esquivel-Velazquez et al, 2015 ; Weichhaus et al, 2015 ), chemokines (Palacios-Arreola et al, 2014 ) and cell adhesion proteins (Spivey et al, 2012 ; Beauchemin and Arabzadeh, 2013 ; Karousou et al, 2014 ; Yu and Elble, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…COL4 was absent from the tumor stroma, with only perivascular COL4 observed (Figure 1E ). Accompanying these changes in ECM composition, heterogeneous breast cancer microenvironments are enriched with hormones (Garcia-Robles et al, 2013 ; Simões et al, 2015 ), growth factors (Mimeault et al, 2007 ; Ye et al, 2009 ; Zheng et al, 2014 ; Ho-Yen et al, 2015 ; Voudouri et al, 2015 ), cytokines (Esquivel-Velazquez et al, 2015 ; Weichhaus et al, 2015 ), chemokines (Palacios-Arreola et al, 2014 ) and cell adhesion proteins (Spivey et al, 2012 ; Beauchemin and Arabzadeh, 2013 ; Karousou et al, 2014 ; Yu and Elble, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that Notch signalling plays a significant role in the development of endocrine therapy resistance [ 18 , 19 , 29 , 30 ]. Notch signalling is partly dependent on the absolute amounts of Notch receptors present in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…Zheng et al . proposed that FN causes epithelial cells to become refractory to tamoxifen by binding to β1 integrin ( 21 , 22 ). Consistent with these reports, we found that patients with luminal type A breast cancer with high levels of FN showed shorter relapse-free survival.…”
Section: Discussionmentioning
confidence: 99%